Penentuan Gaya Tolak Menolak Magnet Antar Dua Magnet Permanet Menggunakan Metode Kesetimbangan Benda - Asih Nugroho, Kuncoro (BERKALA FISIKA, 2010)
Use of magnets vary in life. Use of magnets depending on needs. Magnets can be used from the side: the field is generated, attractive force and repel force between the two magnets. Special utilizing repel forces magnetic one used on the railways to reduce the friction between wheel and rail.One way to determine the amount of repel force magnet is to use the object equilibrium. Two similar magnetic poles will repel. Large repulsion force depends on magnetic field (B) accrued and distance (r) the two magnets. Two magnets with similar poles are placed in the shell will give rise to vertical distance between the magnets to each other.  There is a balance between the repulsive magnetic force with the gravity due to the mass of the magnet when the magnet above the rest. Magnetic repulsive force can be determined for certain r by changing the magnetic mass. Large magnetic gravity on each r can be computed from the gravity due to the magnetic mass.   Keywords: repel force, gravity